Cost Accounting: Accumulation, Analysis, and Use (Book). - Meyer, Philip E. (The Accounting Review, 1982)
Reviews the book "Cost Accounting: Accumulation, Analysis and, Use," by Joseph G. Louderback and Maurice L. Hirsch.